Synthesis of Struvite Fertilizer (MgNH4PO4.6H2O) from Cow Urine and Bittern by Precipitation Technique - Fazira, Zetta; Apriansyah, Ahmad Muhar; Al Attharsyah, Teuku Zibran; Mukhriza, Teuku; Amsi, Utari Yasmine; Hisbullah, Hisbullah (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2024)
The need for fertilizers has significantly increased due to the expanding global population and the mounting pressure on agricultural systems to increase food production. Fertilizers are essential in upgrading soil fertility and increasing crop productivity, making them indispensable in contemporary agriculture. Extensive usage of chemical fertilizers has led to environmental issues such as soil deterioration, water contamination, and the exhaustion of non-renewable resources like phosphate rock. Phosphorus, one of the essential macronutrients for plants, is a critical component of commercial fertilizers. Struvite, with its high phosphate content, presents a viable alternative to conventional fertilizers. Struvite (MgNH4PO46H2O) is a crystalline compound comprising magnesium, ammonium, and phosphate. Cow urine, which contains nitrogen, phosphate, and potassium, can serve as a nutrient source for plants. In the context of fertilizer production, bittern serves as a source of magnesium. This study investigated the production of struvite from cow urine and bittern using a precipitation technique. The study aimed to determine the optimal conditions for maximizing struvite production, focusing on the ratio of cow urine to bittern and the storage duration of cow urine. The research involved the preparation and characterization of raw materials, struvite synthesis, and the analysis of struvite characteristics. The optimal conditions were found to be a molar ratio of cow urine to bittern of 1:1 and a cow urine storage time of one week. UV-VIS spectrophotometry was utilized to analyze phosphate and ammonia contents, yielding optimal values of 72.417 mg/kg and 0.715 mg/kg, respectively. XRF analysis indicated a magnesium content of 26.000 mg/kg. SEM and XRD analyses revealed that the morphology of the struvite was orthorhombic at the optimum conditions. FTIR analysis was used to identify N-H, P-O, and water vibrations.